A COMPARATIVE STUDY BETWEEN WORD WALL AND FLASH CARD TO INCREASE STUDENTS’ VOCABULARY OF VIII GRADE STUDENTS AT SMP NEGERI 5 TOLITOLI - Arni J Timumun (Universitas Madako Tolitoli, 2020)
The aims of this research are to find out whether the Word Wall and Flash Card media can increase students’ vocabulary of eighth grade students at SMPN 5 Tolitoli. The design of this research was true-experimental research. The sample of this research is consisted of 38 students’ is VIII A 19 and VIII B 19, which using random sampling. The data obtained from pre-test and post-test. In the class Word Wall post-test, it found that the mean score of the students is 73,26 was higher than pre-test 52,84 And the mean score of the class Flash Card in post-test is 72,00 was higher than pre-test 40,11. The testing hypothesis showed that the value of t-count was lowest than t-table (0,269<2.028). In Conclusion, there was no significant difference whether the of word wall and flash card in increasing students’ vocabulary at SMPN 5 Tolitoli. Key words: Compare, Word wall, Flash card, Vocabulary